2013
DOI: 10.4137/bci.s13025
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Differences and Similarities between Alzheimer's Disease and the 5XFAD Transgenic Mouse Model of Amyloidosis

Abstract: Transgenic (Tg) mouse models of Alzheimer’s disease (AD) have been extensively used to study the pathophysiology of this dementia and to test the efficacy of drugs to treat AD. The 5XFAD Tg mouse, which contains two presenilin-1 and three amyloid precursor protein (APP) mutations, was designed to rapidly recapitulate a portion of the pathologic alterations present in human AD. APP and its proteolytic peptides, as well as apolipoprotein E and endogenous mouse tau, were investigated in the 5XFAD mice at 3 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 65 publications
7
45
1
2
Order By: Relevance
“…Therefore, these 5xFAD transgenic mice have been acknowledged as a useful model for better understanding the pathogenesis of human Alzheimer’s disease. In agreement with previous reports [22, 24], we found that first signs of amyloidosis and gliosis were detectable in the lower cortex and the corpus callosum of 2.5-month-old 5xFAD mice, although area fractions of GFAP staining and Iba-1 staining did not differ significantly from those of age-matched controls. However, significant increases in both astrocytosis and microgliosis, which occurred in parallel to significant increases in the Aβ area fraction, were found in the lower cortex, as well as in the corpus callosum of 5xFAD mice at the age of 5 months.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, these 5xFAD transgenic mice have been acknowledged as a useful model for better understanding the pathogenesis of human Alzheimer’s disease. In agreement with previous reports [22, 24], we found that first signs of amyloidosis and gliosis were detectable in the lower cortex and the corpus callosum of 2.5-month-old 5xFAD mice, although area fractions of GFAP staining and Iba-1 staining did not differ significantly from those of age-matched controls. However, significant increases in both astrocytosis and microgliosis, which occurred in parallel to significant increases in the Aβ area fraction, were found in the lower cortex, as well as in the corpus callosum of 5xFAD mice at the age of 5 months.…”
Section: Discussionsupporting
confidence: 93%
“…The 5xFAD transgenic mouse was developed by Oakley et al [22] to co-express five familial forms of Alzheimer’s disease [APP K670 N/M671L (Swedish) + I716 V (Florida) + V717I (London) and PS1 M146L + L286 V]. 5xFAD mice are characterised by the early development of Aβ plaques, neuroinflammation, neuronal loss, and memory impairment [2224, 30, 31], all hallmarks of human Alzheimer’s disease. Therefore, these 5xFAD transgenic mice have been acknowledged as a useful model for better understanding the pathogenesis of human Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5XFAD mice overexpress human amyloid precursor protein (APP695) with Swedish (K670N, M671L), Florida (I716V), and London (V717I) familial AD mutations, also with mutant human presenilin‐1 (M146L, L286V) controlled by murine Thy‐1 promoter . 5XFAD mice generate Aβ 1–42 almost exclusively, rapidly accumulate amyloid plaque formation, and also recapitulate major pathologic and behavioral characteristics of AD . 5XFAD mice were backcrossed into the C57BL/6J background at least 10 generations to reduce genetic variation.…”
Section: Methodsmentioning
confidence: 99%
“…15 5XFAD mice generate Ab 1-42 almost exclusively, rapidly accumulate amyloid plaque formation, and also recapitulate major pathologic and behavioral characteristics of AD. [15][16][17] 5XFAD mice were backcrossed into the C57BL/6J background at least 10 generations to reduce genetic variation. The mice C57BL/6J (male) were purchased from SLC Japan (Shizuoka, Japan).…”
Section: Methods Animalsmentioning
confidence: 99%